Behind the Chain of Poverty: Social and Economic Conflicts that Oppress Fishing Communities - Novakarti, Ovy; Asengbaramae, Rowiyah (Talenta Publisher, 2025)
Fishing communities in Indonesia are often the most vulnerable social group to poverty and marginalization. Although the marine sector has great potential for the economy, small and traditional fishermen are often trapped in a cycle of poverty that is difficult to break. This article examines the poverty trap experienced by fishing communities through the perspective of social conflict theory. Using a qualitative approach that includes data collection through a literature review, this study analyzes how the unequal distribution of resources and power in the fisheries sector leads to exploitation and worsens the socio-economic conditions of fishers. Factors such as dependence on middlemen, market price instability, unfavorable fisheries policies, and marine ecosystem degradation due to overfishing and climate change further strengthen the poverty chain. In addition, internal conflicts within fishing communities also play a role in exacerbating poverty conditions. This article seeks to uncover the dynamics of social and economic conflicts that plague fishing communities, and offers solutions based on community empowerment and fairer policy reforms